Which bacterial toxins are worthy of validation as markers in colorectal cancer screening? A critical review - Mezerova, Kristyna; Raclavsky, Vladislav; Stary, Lubomir (Biomedical papers, 2022)
Appropriate screening of early asymptomatic cases can reduce the disease burden and mortality rate of sporadic colorectal cancer (CRC) significantly. Currently, fecal occult blood testing (FOBT) is able to detect up to 80% of asymptomatic cases in the population aged 50+. Therefore, there is still a demand for new screening tests that would complement FOBT, mainly by detecting at least a part of the FOBT-negative CRC and adenoma cases, or possibly by identifying person at increased risk of sporadic CRC in order to offer them tailored follow-up. Among the potential markers studied, our knowledge has advanced at most in toxigenic gram-negative bacteria. In this review, we assess their potential critically and recommend those best suited for prospective evaluation of their true ability to increase the sensitivity of FOBT when combined during general population screening. In our opinion, colibactin and Bacteroides fragilis toxin are the best candidates, possibly complemented by the cytotoxic necrotizing factor (CNF).
Keywords: colorectal cancer; enterotixin; colibactin; cytolethal distending toxin; cytotoxic necrotizing factor; cycle inhibiting factor; Bacteroides fragilis toxin